Economic assessment of carbon capture by minichannel absorbers. Issue 2 (31st August 2017) - Yang, Ziqiang; Khan, Tariq S.; Alshehhi, Mohamed; AlWahedi, Yasser F.
Abstract : In this work, a physio‐economic model supported by lab‐scale experiments assessing the economic viability of minichannel based carbon capture units is presented. The net present value of (capital and operating) costs (NPVC) ensued throughout the plant life is selected as the benchmarking parameter. An optimization problem is formulated and solved with the objective of minimizing the NPVC of the unit subject to constraints imposed by the physics of absorption and pressure drop limits; both of which are captured via experimentally deduced empirical correlations. The results show that the minichannel absorbers are economically competitive to conventional systems for low capacity CO2 capture achieving savings ranging from ∼50% to 3% for plant capacities ranging from 5 to 50 MMSCFD, respectively, primarily due to their lower capital costs. At higher plant capacities, the higher operating costs of the minichannel units dominate their NPVC and as such lead them to lose their competitiveness. © 2017 American Institute of Chemical Engineers AIChE J, 64: 620–631, 2018